Financing of NCD Prevention in LMICs: Iran Case Study - Ali Islam Ghauri; Tajwar Awan; Kassim Nishtar; Saba Amjad (Journal of the Pakistan Medical Association, 2026)
Objective: This case study is part of a series of 10 case studies from low-and-middle-income countries that were carried out to describe the enablers, dynamics, and challenges of financing prevention programmes to counter noncommunicable diseases, and to identify promising practices and common threads and trends in these countries. Prevention programmes are increasingly seen as critical for tackling the rising burden of non-communicable diseases (NCDs), but tend to be under-prioritised and under-funded, particularly in low and middle-income countries. The objective of this study is to critically assess the NCD prevention efforts made by the Iranian government over the years with a particular focus on cardiovascular diseases, cancers, chronic pulmonary diseases, diabetes, and psychiatric disorders. Methods: The available literature on NCD prevention, funding, policy formulation, and recommendations was reviewed and selected publications were thematically organized into categories of analysis that were refined based on the emerging evidence. Later, a specific search was undertaken for broader literature, including policy frameworks on NCDs in Iran. An in-depth interview was carried out with an official from the health ministry to gain insights into the government’s perspective and approach. Results: Iran’s NCD prevention efforts are guided by a National Action Plan developed by the Iranian Non- Communicable Diseases Committee, which was set up by the high-powered Supreme Council for Health and Food Security (SCHFS). Under the 6th National Development Plan (2016-2021), Iran announced a US 480 million increase in its NCDs budget for the next five years. The health ministry determines the financing requirement for every programme and campaign that is to run on the ground and the government issues the required funds. The cost of NCD prevention programmes is minimal in most cases since they are integrated into an already existing public healthcare system. Iran’s NCD efforts operate without any external development assistance for health, and the government’s plans are further restricted due to international trade sanctions. Conclusion: In spite of trade sanctions, COVID-19 triggered economic meltdown, and zero international assistance for health, Iran has made considerable progress in preventing and containing the spread of NCDs. International support, easing of trade sanctions, and improvements in the current PHC can reduce the economic burden of the NCDs, as well as support the government’s ability to improve the condition of the existing health care systems and networks. Keywords: Diseases, Stress, COVID-19, Diabetes, Management, Policy